EFFICIENCY OF CAROTINE-CHLOROPHYLLIC COMPLEXES USE IN A-HYPOVITAMINOSIS OF POULTRY - Ljudmila Reznichenko; Inessa Jakovleva; Aleksej Reznichenko; Nina Denisova; Nadezhda Savushkina; Tatyana Shevchenko; Elena Shentseva; Sergey Zherebnenko (Belgorod National Research University, 2017)
As is known, poultry is very sensitive to the lack of vitamins in the case of stress or diseases, reducing food intake and reducing intestinal absorption of vitamins. Deficiency of carotene and vitamin A leads to various diseases of young animals, a drastic reduction in the productivity and fertility of adult animals. The principal purpose of this study was to investigate the possibility of using chloroprenol as a vitamin supplement in diets of broiler chickens for the prevention of A-vitamin deficiencies and improve the commercial quality of poultry products. In accordance with desired goal we have estimated the clinical-biochemical status of the broiler chickens under production-line conditions, defined the optimal dosages of chloroprenol for the broiler chicken, determined the effect of the drug on the morphological and biochemical parameters of blood, studied their effect on the natural resistance parameters of the body, accumulation of biological active substances in the liver, viability and productivity. It should be noted that before experimentation a significant increase in aspartate aminotransferase was found in the serum of all chickens, indicating toxic liver injury and vitamin A reduction - insufficient intake of this vitamin in the body of the poultry. After administration of the highest doses of chloroprenol (5.0 and 10.0 ml/l water) a significant increase in vitamin A was observed (on 24.2 and 27.3%) in the blood serum and (on 20.5 and 18.3%) in the liver. At the end of the experimental period phagocytic activity of pseudoeosinophiles was increased (23.6 and 26.1%) in comparison with the control. Based on the results of the research we have identified the optimal dose chloroprenol - 5.0 ml/l water, because the a higher dose does not give a significant increase in poultry weight and enhance the natural resistance, and the low dose is less effective. Therefore, we have substantiated efficiency of using chloroprenol for broiler chickens as a preventive agent for A-hypovitaminosis.